History of Banach Spaces and Linear Operators - Pietsch, Albrecht; SpringerLink (Online service) (Boston, MA : Birkhäuser Boston, 2007)
Named for Banach, one of the great mathematicians of the twentieth century, the concept of Banach spaces figures prominently in the study of functional analysis with applications to integral and differential equations, approximation theory, harmonic analysis, convex geometry, numerical mathematics, analytic complexity, and probability theory. Written by a distinguished specialist in functional analysis, this book presents a comprehensive treatment of the history of Banach spaces and (abstract bounded) linear operators. While other historical texts on the subject focus on developments before 1950, this one is mainly devoted to the second half of the 20th century. Banach space theory is presented in a broad mathematical context, using tools from such areas as set theory, topology, algebra, combinatorics, probability theory, and logic. Equal emphasis is given to both spaces and operators. Numerous examples and counterexamples elucidate the scope of the underlying concepts. As a stimulus for further research, the text also contains many problems which have not been previously solved. The book may serve as a reference for researchers and as an introduction for graduate students who want to learn Banach space theory with some historical flavor. Helpful information is also provided for professors preparing their own lectures on functional analysis.
The Birth of Banach Spaces -- Historical Roots and Basic Results -- Topological Concepts - Weak Topologies -- Classical Banach Spaces -- Basic Results from the Post-Banach Period -- Modern Banach Space Theory - Selected Topics -- Miscellaneous Topics -- Mathematics Is Made by Mathematicians.
Keywords: MATHEMATICS; FUNCTIONAL ANALYSIS; OPERATOR THEORY; MATHEMATICS_{DOLLAR}XHISTORY.; MATHEMATICS; HISTORY OF MATHEMATICS; FUNCTIONAL ANALYSIS; OPERATOR THEORY